Factors of Socio-Economic Development of Partially Recognized and Unrecognized Republics of the Caucasus - A. G. Shelomentsev; K. S. Goncharova (Vestnik MGIMO-Universiteta)
Particular and general factors determine the dynamics and trends of endogenous development of three unrecognized and partially recognized republics of the Caucasus the Republic of South Ossetia (RSO), Abkhazia, and the Nagorno-Karabakh Republic. The article identifies critical factors and assesses prospects for endogenous socio-economic development of an unrecognized and partially recognized Republics of the Caucasus. It uses comparative and statistical methods, namely, one-factor analysis of variance (ANOVA) and the Kraskel-Wallis Criterion. A database developed for this study uses a set of indicators of the UN Sustainable Development Goals (SDGs) for 2007 to 2019 as a formalized universal and balanced system of global determinants. We found that differences in the achieved UN SDGs indicators can be accounted for by the variety of each state's initially socio-economic situation (the effect of a differentiated base). At the same time, the research shows that the dynamics of the development of the Caucasian republics are similar, which determines a commonality of trends of their future (while maintaining current conditions and circumstances). The study results expand our understanding of the development of unrecognized and partially recognized states. It shows that one has to consider this propensity of the Caucasian states to self-development when justifying measures for improving their socioeconomic situation and increasing the effectiveness of investment programs implemented jointly with the Russian Federation to promote the socio-economic development of the RSO and the Republic of Abkhazia.